An assessment of crop water productivity in the Indus and Ganges River Basins: current status and scope for improvement - Xueliang Cai; Sharma, Bharat R.; Matin, Mir Abdul; Sharma, D.; Gunasinghe, Sarath (International Water Management Institute, 2010)
The Indus and Ganges River Basin, being the most populous in the world, is under extreme pressure to sustain food security. Production resources including water are being exploited to various levels from underdevelopment to heavy overexploitation. This report provides a bird?s eye view of the basin and focuses on the nexus between agricultural production and water consumption, making it possible to pinpoint the areas with high/low water productivity and identify the factors behind this, which helps to promote informed decision making in light of environmental sustainability.